Capability approach to public-space harassment of women: Evidence from India and Bangladesh - Günseli Berik; Haimanti Bhattacharya; Tejinder Pal Singh; Aashima Sinha; Jacqueline Strenio; Sharin Shajahan Naomi; Sharon Talboys (The University of Utah, Department of Economics, 2022)
Sexual harassment of women and girls in streets and other public spaces is often trivialized by the label of "eve teasing" in South Asia. While there exists a volume of research on intimate partner or domestic violence in South Asia, the literature on public-space harassment (PSH) is rather sparse. Based on 2021 surveys in Bangladesh and India, this paper examines the prevalence and consequences of public-space harassment using the Capability Approach. We used an online survey and snowball sampling through social media to generate both quantitative and qualitative information. We analyzed the data descriptively and coded the open-ended responses based on human capability themes. The responses to questions about twelve specific forms of harassment indicate that the experience of at least one form of PSH is ubiquitous in both country samples. We find that PSH deprives women of a range of capabilities: to lead lives free of violence, to enjoy emotional well-being, to be physically mobile, to seek educational opportunities, and to earn a living. Overall, women indicated that PSH resulted in wide-ranging restrictions on their freedom. Respondents also articulated future directions for action to reduce experiences of PSH, including education, awareness, and legal measures.
Keywords: B54; D63; I31; 330; Sexual Harassment; Human Capabilities; Gender; India; Bangladesh